2005
DOI: 10.1111/j.1464-5491.2004.01404.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic profiles of biphasic insulin aspart 30/70 and 70/30 in patients with Type 1 diabetes: a randomized double‐blinded crossover study

Abstract: On day 15 BIAsp70 was associated with a shorter Tmax, and more than 40% elevated Cmax. Comparing with BIAsp30, AUC(0-24 h) and AUCdinner(0-6 h) were increased by 25% and 28%, respectively, but AUCdinner (6-14 h) was markedly lower for BIAsp70 [BIAsp30/BIAsp70: 1.9; 95% CI (1.42, 2.55)]. Similar findings were also observed on day 1. The fasting or pre-meal serum insulin levels on day 15 tended to be higher with BIAsp30, but the differences were not statistically significant. CONCLUSIONS The pharmacokinetic prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…The data came from a previously published study of a biphasic insulin aspart (IAsp) preparation [5]. The complete 24-h serum insulin concentrations measured in the 20 type 1 diabetes subjects, who were given three daily s.c. injections at different sites within the abdominal region, are presented in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data came from a previously published study of a biphasic insulin aspart (IAsp) preparation [5]. The complete 24-h serum insulin concentrations measured in the 20 type 1 diabetes subjects, who were given three daily s.c. injections at different sites within the abdominal region, are presented in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Acknowledgements The authors are grateful to J. S. Christiansen and J.-W. Chen for carrying out the clinical trial [5] that allowed us to perform this research. This research was supported by The Danish Ministry of Science, Technology and Innovation, and Novo Nordisk.…”
mentioning
confidence: 99%
“…An earlier and less comprehensive double‐blind crossover study of 26 patients with type 1 diabetes found insulin C max values were approximately twice as high after all three main meals during thrice‐daily BIAsp 70 treatment than during thrice‐daily BIAsp 30 treatment (figure 2) [24]. Furthermore, the time to C max ( t max ) was significantly shorter (p < 0.05) after all three meals with BIAsp 70: 60 min for all three meals compared with 90, 75 and 82.5 min for breakfast, lunch and dinner, respectively, for BIAsp 30 [24]. As in the Heise et al .…”
Section: Pharmacology Of Mid‐ and High‐ratio Premix Insulin Analoguesmentioning
confidence: 98%
“…AUC 6–14 h was markedly lower for BIAsp 70 than for BIAsp 30 (BIAsp 30/BIAsp 70 = 1.9; 95% CI [1.42, 2.55]; P <0.002). [13] The time to maximum insulin concentration ( T max ) was significantly shorter after all three meals with BIAsp 70 ( P <0.05). Peak levels for both BIAsp 30 and BIAsp 70 were seen to increase with each daily injection over this 15-day period, suggesting a degree of accumulation that needs to be taken into consideration if a TID dose is to be prescribed.…”
Section: Clinical Evidence For Mid-/high-ratio Premix Analogs For Intmentioning
confidence: 99%
“…Peak levels for both BIAsp 30 and BIAsp 70 were seen to increase with each daily injection over this 15-day period, suggesting a degree of accumulation that needs to be taken into consideration if a TID dose is to be prescribed. [13]…”
Section: Clinical Evidence For Mid-/high-ratio Premix Analogs For Intmentioning
confidence: 99%